The Yo-Yo IR2 test in professional basketball players - Gürses, Veli Volkan; Akgül, Mustafa Şakir; Ceylan, Bayram; Baydil, Bilgehan (Uluslararasi Insan Bilimleri Dergisi, 2018)
The aim of this study was to investigate the relationship between direct method and indirect method (Yo-Yo Intermittent Recovery Test Level II) that are used to determine aerobic capacity and endurance. Fourteen basketball players (22.49 ±04.82 year-old with the height 192.36±5.90 cm, weight 89.21±7.6 kg, Body fat percentage 11.07 ± 1.82 %) voluntarily participated in this study. Yo-Yo Intermittent Recovery Test Level II protocol (YIRT 2) was implemented to participants. Distance covered by the athletes, estimated VO2max, direct VO2max, Anaerobic threshold VO2 and Anaerobic threshold heart rate (HRAT) values were recorded. Direct VO2max and other respiratory parameters were measured with telemetric gas analyzer. After 5 minute rest in supine position heart rates (HRrest), rest lactate levels (LArest) and maximal heart rate (HRmax) during the test and post test lactate levels (LApost) were measured. Pearson Correlation Test was used to determine the relationship between the variables. P value was set at 0,05. According to the findings, positively significant large correlation was found between estimated VO2max and direct VO2max(r = 0.504, p < 0.05), HRmax (r = 0.501, p < 0.05), positively significant large correlation was found between distance and Direct VO2max(r = 0.521, p < 0.05), HRmax (r = 0.516, p < 0.05). There is no significant relationship except above-mentioned variables (p<0.05). YIRT2 can guess VO2max of professional male basketball players and can be used to evaluate endurance.
Keywords: Aerobic capacity, Endurance tests, Yo-Yo Intermittent Recovery Test, VO2max, Basketball; Physical Education and Sport; Coaching Education